Association of rs2249863 and rs1233334 polymorphisms of the upstream region of HLA-G gene with recurrent spontaneous abortion in women from Northwest of Iran during 2018-2019 - Leili Khasevani; Mohammad Khalaj-Kondori; Baharak Ebrahimi Behnam (Mashhad University of Medical Sciences, 2020)
Introduction: Genetic polymorphisms are one of the possible causes of recurrent abortion with unknown cause. This study was performed with aim to investigate the association and frequency of rs2249863 and rs1233334 polymorphisms of the upstream region of HLA-G gene with the recurrent spontaneous abortion in women from Northwest of Iran. Methods: This case-control study was performed on 160 women from Northwest of Iran referring to the Madar infertility clinic of Tabriz between 2018 and 2019. Among them, 80 women with a history of recurrent spontaneous abortion (at least 2 abortions) were considered as case group and 80 women with at least one child and without any history of miscarriage as control group. After collecting blood samples, genome DNA was extracted and the polymorphisms were evaluated by PCR and sequencing technique. Data were analyzed using SPSS software (version 22) and Fisher test. P <0.05 was considered statistically significant.     Results: The frequencies of allele G and genotype GG in the rs2249863 polymorphism were significantly different between the case and control groups (P<0.05). In the rs1233334 polymorphism, although the frequencies of allele C and genotype CC were different between the case and control groups, but the differences were not statistically significant (P>0.05). Moreover, haplotype analysis identified the CG as the commonest haplotype that its frequency was significantly different between the case and control groups (P<0.05). Conclusion: The rs2249863 polymorphism and CG haplotype of the rs2249863 and rs1233334 polymorphisms are associated with the recurrent spontaneous abortion in the studied population and they could be considered as potential risk factors for the disease.